First record of Sigara (Tropocorixa) rubyi (Hungeford) (Heteroptera: Corixidae) in Chile, and comments on the nomenclature of two South American Sigara Fabricius - CAMPODONICO, Juan F.; FAÚNDEZ, Eduardo I. (My University, 2019)
Sigara (Tropocorixa) rubyi (Hungerford, 1928), previously known from Argentina and Uruguay, is recorded for the first time in Chile, in Valparaíso Region. The correct spelling of this species and Sigara (Tropocorixa) hosfordi (Hungerford, 1928) is commented.
Keywords: faunistics. nepomorpha. nomenclature. south america